On the Issue of Bulgarian Public Holidays - Nedeleva, Petya (Yearbook of the Law Department, 2021)
The festive calendar is a reflection of the understandings, values and history of a people and country, a sign to the next generations about the difficulties and victories of the past, an example of what they should value, what they should not forget and what they should learn from. Until the establishment of the Third Bulgarian State, the holiday calendar of the Bulgarian society consisted primarily of religious and traditional holidays, which were preserved as a main component of the holiday calendar even after the Liberation. To them are added holidays related to the monarchical institution, as well as important historical events for the Bulgarian people. Generally, public holidays are the designated important dates and non-working days in our annual national calendar, and the national holiday should be the most important day among them. Such an occasion is undoubtedly the adoption of the first democratic Bulgarian Constitution on April 16, 1879, which should not just be a day in Bulgarian history, but a national holiday of the Bulgarian state. If we respect the Bulgarian institutions, statehood and independence, we must give due importance and respect to this date.